O conceito de biblioteconomia em L.-A. Constantin (1779-1844) e a difusão do seu trabalho - Crispim, Éderson Ferreira (2020)
The elaboration of a concept in librarianship found in the work of a bookseller in the first half of the 19th century in France, gave rise, perhaps, to micronarratives around the establishment of a discipline and a career to develop. A career that, as it were, has been changing its set of activities since the last four centuries. In a word, countless characters, from the most famous to a few remembered, have become, to a greater or lesser extent, important operators in describing a special type of work, which, historically, has always manifested itself. Or, that is to say, it prospered more, at least, in places where the creation of universities, knowledge of papermaking and freedom of the press were possible. On this way, such a historical perspective that we elaborate here involving the area of librarianship, it was only possible for us to build based on the elaboration of a concept in context. Thus, we work with the hypothesis that, until further notice, the first work of this nature to use the word in the title was the Bibliothéconomie: Instructions sur l'Arrangement, la Conservation et l'Administration des Bibliothèques by the German-French bookseller Leopold Auguste Constantin Hesse (1779-1844) originally published in 1839 in the city of Paris and modified in 1841